ALISIS FAKTOR PENDORONG PERILAKU PLAGIARISME AKADEMIK DI KALANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN SOSIOLOGI UNIVERSITAS MATARAM - Haniza Febriani; Musahidin; Hurniati; Eka Novita; Sumitro; Rakhmat Nur Adhi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to understand and analyze the various factors that trigger academic plagiarism among students in the Sociology Education Study Program at the University of Mataram. This study uses a qualitative approach with semi-structured interviews to explore the views and experiences of informants regarding this dishonest behavior. The research findings indicate that although students already understand the basic concept of plagiarism, technological advances have changed the way plagiarism occurs. In addition to copying from the internet or imitating friends, a new trend has emerged that uses generative artificial intelligence (AI) fully (100%) without involving paraphrasing or adding references. This phenomenon is analyzed using the Fraud Triangle theory, which has three main factors: pressure, opportunity, and rationalization. Pressure arises from internal factors, such as procrastination and poor time management, which occur amidst the large amount of work to be done. Opportunities arise from easy access to the digital world, insufficient supervision, few penalties, and a lack of tools to detect AI. These conditions encourage the direct use of AI, because limited technical skills in scientific writing make students feel this is normal. Overall, addressing plagiarism requires more than just reactive administrative policies. Study programs must implement a comprehensive preventative approach from the beginning of the course by providing training in academic writing and reference management, implementing sanctions routinely and consistently, and strengthening the role of lecturers in providing clear explanations of academic assignments while still respecting students' independent thinking skills to maintain academic integrity.